Representasi Visual Budaya Kolombia Pada Film Animasi “Encanto” (SENIMAN: Jurnal Publikasi Desain Komunikasi Visual, 2023)
This study analyzes the system of signs and meanings of Colombian culture in the animated film "Encanto" from Disney Animation. The film takes inspiration from Latin American culture, specifically Colombia, focusing on the Madrigal family who have magical powers and live in a hidden village. A qualitative approach with descriptive-interpretative methods is used with content analysis, based on Charles Sander Pierce's semiotic concept which includes icons, indexes, and symbols. Data obtained through observation and literature study. The results of the study show that elements of Colombian culture, such as language, clothing, food, and traditions, are reflected in film characters and scenes. Examples of representation include the Arepa dining area, Cali salsa dancing, Colombian music, and Colombian-style mountain scenery. Thus, Encanto succeeded in communicating Colombian cultural messages through visual cues in the animated film.